Effectiveness of Visual Media Use in Islamic Religious Education Learning in Junior High School - Alfurqan Alfurqan; Marsita Dwi Susanti (Attanwir : Jurnal Keislaman dan Pendidikan, 2021)
Science and technology are progressing rapidly. These advances have brought significant changes in various aspects of human life, both in the social, economic, cultural and educational fields. For education not to be left behind, adjustments are needed, especially related to learning factors in the classroom. The learning process is a communication process. Sometimes in the learning process, there is a communication failure. To avoid communication failure, teachers need to make use of interesting learning media. Visual media is a tool that teachers use to transmit messages from the sender to the recipient using the sense of vision. This study uses descriptive qualitative research. This research was conducted at SMP Negeri 2 Sawahlunto. The subjects of the study were Islamic Religious Education Teachers and students of SMP Negeri 2 Sawahlunto. Data collection techniques used are observation, interview, documentation. This research generates (1) passionate and enthusiastic students when teachers use visual media in the learning process. (2) Visual media can make it easier for students to remember lesson materials. (3) Visual media in the form of PowerPoints and concept maps used by teachers in the lesson process can display a concrete picture of material, to improve students' thinking power.